A cloud service for trust management in cognitive radio networks. (1st January 2014) - Bhattacharjee, Shameek; Marinescu, Dan C.
Transferring computations for cognitive radio network (CRN) management to a computer cloud opens the possibility to implement new, possibly more accurate and powerful resource management strategies. Algorithms to discover communication channels currently in use by a primary transmitter and identify malicious nodes with high probability could be based on past history; when the trust is computed by the mobile devices this approach is not feasible because such algorithms require massive amounts of data and intensive computations. In this paper, we introduce a cloud service based on a novel trust management algorithm; this solution, applicable to infrastructure-based and to ad hoc CRNs, ensures secure and robust operation in the presence of malicious nodes. We discuss the economic benefits, scalability and robustness of the proposed service for different network configurations and parameters.